2012
DOI: 10.1111/j.1469-8137.2012.04108.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterns of soil pathogens in declining Mediterranean forests: implications for tree species regeneration

Abstract: Summary• Soil-borne pathogens are a key component of the belowground community because of the significance of their ecological and socio-economic impacts. However, very little is known about the complexity of their distribution patterns in natural systems. Here, we explored the patterns, causes and ecological consequences of spatial variability in pathogen abundance in Mediterranean forests affected by oak decline.• We used spatially explicit neighborhood models to predict the abundance of soil-borne pathogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
103
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(108 citation statements)
references
References 59 publications
5
103
0
Order By: Relevance
“…We found that in woodland sites an important fraction of Q. suber seedlings did not show any ECM colonization (25% of the seedlings) or had low colonization values (37% of the seedlings had <20% of root tips colonized). Therefore, in these sites a higher seedling investment in ECM associations in response to tree decline could be justified in terms of an expected gain in performance, particularly taking into account that seedlings established in defoliated and dead neighborhoods are severely impaired due to stressful microclimatic conditions (Ibáñez et al, 2015) and high soil-borne pathogen loads (Gómez-Aparicio et al, 2012). This result also agrees with the ''intermediate host-plant stress hypothesis'' (Swaty et al, 2004), which postulates that stress can promote the establishment of mycorrhizal associations, at least until a certain threshold at which hosts can no longer support the C costs of the association.…”
Section: The Role Of Canopy Composition and Health Status As Direct Dmentioning
confidence: 99%
“…We found that in woodland sites an important fraction of Q. suber seedlings did not show any ECM colonization (25% of the seedlings) or had low colonization values (37% of the seedlings had <20% of root tips colonized). Therefore, in these sites a higher seedling investment in ECM associations in response to tree decline could be justified in terms of an expected gain in performance, particularly taking into account that seedlings established in defoliated and dead neighborhoods are severely impaired due to stressful microclimatic conditions (Ibáñez et al, 2015) and high soil-borne pathogen loads (Gómez-Aparicio et al, 2012). This result also agrees with the ''intermediate host-plant stress hypothesis'' (Swaty et al, 2004), which postulates that stress can promote the establishment of mycorrhizal associations, at least until a certain threshold at which hosts can no longer support the C costs of the association.…”
Section: The Role Of Canopy Composition and Health Status As Direct Dmentioning
confidence: 99%
“…The fungal and oomycete pathogens are predicted to account a greater share of the disease catastrophes caused by ecological degradations (Giraud et al, 2010; Fisher et al, 2012). Upsurges of epidemics caused by soil microbiota (Klironomos, 2002), particularly the species of the oomycete necrotroph Pythium may critically affect the demography and diversity of an ecosystem (Gómez-Aparicio et al, 2012). Thus, the ongoing habitat fragmentation and climate change may trigger a drastic shift in the reproductive strategy, host resistance and demography in natural populations in the near future.…”
Section: Introductionmentioning
confidence: 99%
“…From the few studies that have focused on pathogen populations, it is becoming clear that species within the oomycete genus Pythium can be significant regulators of native plant communities (Mills and Bever 1998; Packer and Clay 2000, 2003, 2004; Augspurger and Wilkinson 2007; Gómez-Aparicio et al. 2012) and, at the same time, facilitate invasiveness of a number of plant species (Reinhart et al. 2005, 2010a,b, 2011; Reinhart and Clay 2009; Butof and Bruelheie 2011).…”
Section: Introductionmentioning
confidence: 99%